EFL Writing as a Lens for Exploring Sustainability Awareness and Community Resilience - Syahabuddin, Khairiah (Jurnal Kolaborasi Akademika, 2026)
Academic stress is a common challenge among university students and may negatively affect psychological well-being and academic performance. Resilience plays a crucial protective role in helping students adapt and recover from academic pressure. This study aimed to examine the effect of mindfulness on resilience among students experiencing moderate to high levels of academic stress. A quantitative approach with a correlational–predictive design was employed, involving 250 university students from several universities in Indonesia, selected using the Perceived Stress Scale-10 (PSS-10). Data were collected using the Five Facet Mindfulness Questionnaire (FFMQ) and the Connor–Davidson Resilience Scale (CD-RISC-25), and analyzed using simple linear regression. The results indicated that mindfulness had a positive and significant effect on resilience (β = 0.673, p < 0.001), accounting for 45.3% of the variance in resilience. The novelty of this study lies in its focus on students with moderate to high academic stress and in positioning mindfulness as a key psychological predictor of resilience rather than merely a stress-reduction strategy. These findings provide practical implications for the development of mindfulness-based counseling and intervention programs in higher education settings.